Egyptian Handicrafts Clusters: Barriers to Development & Suggested Policy Reforms - Mohamed Soliman Mohamed, Amal (AUC Knowledge Fountain, 2022)
Egypt has a large number of handicrafts clusters, greater than any other industrial clusters in the country. Handicrafts clusters, also known as Creative or artisans’ clusters, are geographic concentrations of households that produce a variety of handmade goods. Such goods include, inter alia, wood works, metal works, stones, and handmade textiles. They contribute to employment creation and poverty alleviation, especially in rural and deprived areas. The development of handicrafts clusters has been the focus of many institutions including World Bank, United Nations Industrial Development Organization (UNIDO), Micro, Small & Medium Enterprise Development Agency (MSMEDA), and Ministry of Trade & Industry; however, the overall impact of the sector in the country is inadequate. Therefore, the main purposes of this study are to: first, investigate the main barriers that hinder the development of Egyptian handicrafts clusters; second, determine this sector’s key needs to thrive and grow, third, to suggest some reform policies that could be beneficial for the sector’s development. In order to tackle the aforementioned objectives, fifteen semi-structured interviews have been conducted with artisans from different creative industrial clusters, as well as public officials who are in charge of developing handicrafts clusters in Egypt. The analysis illustrates several obstacles such as the absence of coordination between development organizations; the poor relevance of interventions to the sector needs; poor access to markets and business models; poor marketing skills and opportunities; low income and high vulnerability of artisans and weak regulations. The study highlights the need for an institutional body managing the sector and for accurate data about the field, and artisans’ social protection among others. Therefore, a distinct way is paved for policymakers to set up sustainable solutions and mechanisms to remove these barriers to enhance the clusters’ economic and social performance.